Grouting Fractured Coal Permeability Evolution Based on Industrial CT Scanning - Li Tao; Yao Banghua; Liu Yong; Wang Dengke (Geofluids)
Gas extraction from coal seams in China faces various middle-term and long-term problems, such as the poor sealing quality and low extraction rate. The mean gas extraction concentration is only 30%. Studying the flowing laws of the grout and fracture plugging mechanism is of important significance to improve the sealing quality and increase the gas extraction efficiency. For this reason, a new coal-based grouting material was prepared in this study, and its parameters such as viscosity were tested. Moreover, a grouting theoretical model with considerations of the flowing of the grout and coal fracture plugging by migration and deposition of slurry particles was constructed. The crack distribution before and after the grouting of fractured coal samples was scanned with an industrial CT, and the fracture distribution of coal samples was reconstructed using an independently compiled MATLAB program. Meanwhile, the variations of the coal permeability before and after the grouting were tested. On this basis, this study built a numerical calculation model of the grouting in fractured coal samples to simulate the leakage stoppage and permeability reduction mechanism of the coal-based sealing material grouting. Results demonstrate that (1) according to the experimental test results, the new coal-based grouting materials achieve a good fracture plugging effect, and the fractures in coal samples after the grouting are filled densely by the grouting particles. (2) According to the simulation results, the permeability of grouting coal samples declines quickly and then tends to be stable. The overall permeability of coal samples and the fracture permeability are decreased by 93.5% and more than 99.9% in average, respectively. (3) Influences of the grouting pressure on the permeability variation of coal samples were investigated through a numerical simulation. It was found that a reasonable grouting pressure for coal samples is about 0.3 MPa. (4) The numerical simulation reproduces the whole process of the grout flowing and the fracture filling. The variation laws of the diffusion and the permeability of the grout which are calculated through a numerical simulation agree well with the experimental results, which verifies the reasonability of the model. Research conclusions can provide important significance in theory and practice to disclose the leakage stoppage and the permeability reduction mechanism of the borehole grouting during the gas extraction and strengthen the sealing effects of extraction boreholes.